The distribution and ecology of the West African polygonaceae (2003)
The Polygonaceae is polymorphic but natural in floral characters. It occupies a wide range of habitats in West Africa. The lowland rainforests provide a suitable habitat for two species namely Afrabrunnlchia credo and Symmeria paniculata while five species are confined to the highlands- Harpagocarpus snowdenii. Rumex bequeartii. R. abyssinicus Persicaria nepalensis and P. selosula. A few of the species e.g. Polygonunt pleheium. Oxygonum sinuatarn and P. limbata have a narrow distributional range being restricted to the drier regions of the Northern ones of Nigeria and Ghana usually in dry to wet riverbanks and ditches Four species are widespread in the sub region. These are Antigonon leptopus. P. senegalensis. P. attenuata. and P. salicifolia Persicaria senegalensis forma albotomentosa has a wider distribution than its other form P. senegalensis forma senegalensis occurring at sea level to as high as 1140m in the Cameroon Mountains and the Mambilla plateau.